Tests of (abuse of) domination: the Danish cement industry - Lisbeth Funding la Cour; H. Peter Møllegaard (Copenhagen Business School (CBS), Department of Economics, 2000)
We test econometrically whether the sole Danish producer of cement holds a dominant position in the Danish market for (grey) cement. In import penetration tests, we find that its pricing and quantity decisions are independent of import price and quantity, implying that it can act to a considerable extent independently of its competitors. We also test whether it can act independently of its customers and find that its demand is inelastic with respect to its price. It thus holds a dominant position in the sense of the European Court of Justice. Having established dominance, we go on to illustrate that based on our data, it is difficult to conclude that it has abused its dominant position in the sense of the Court.
hdl:10398/7560
Keywords: K21; L41; L61; 330; Dominant position; econometric tests; excessive pricing; cement